Overcoming genetic paucity of Camelina sativa: possibilities for interspecific hybridization conditioned by the genus evolution pathway - Blume, Rostyslav Y.; Kalendar, Ruslan; Guo, Liang; Cahoon, Edgar B.; Blume, Yaroslav B. (Frontiers in Plant Science, 2023)
Camelina or false flax (Camelina sativa) is an emerging oilseed crop and a feedstock for biofuel production. This species is believed to originate from Western Asian and Eastern European region, where the center of diversity of Camelina genus is located. Cultivated Camelina species arose via a series of polyploidization events, serving as bottlenecks narrowing genetic diversity of the species. The genetic paucity of C. sativa is foreseen as the most crucial limitation for successful breeding and improvement of this crop. A potential solution to this challenge could be gene introgression from Camelina wild species or from resynthesized allohexaploid C. sativa. However, both approaches would require a complete comprehension of the evolutionary trajectories that led to C. sativa origin. Although there are some studies discussing the origin and evolution of Camelina hexaploid species, final conclusions have not been made yet. Here we propose the most complete integrated evolutionary model for the Camelina genus based on the most recently described findings, which enables efficient improvement of C. sativa via the interspecific hybridization with its wild relatives. We also discuss issues of interspecific and intergeneric hybridization, aimed on improving C. sativa and overcoming the genetic paucity of this crop. The proposed comprehensive evolutionary model of Camelina species indicates that a newly described species Camelina neglecta has a key role in origin of tetra-and hexaploids, all of which have two C. neglecta-based sub-genomes.Understanding of species evolution within the Camelina genus provides insights into further research on C. sativa improvements via gene introgression from wild species, and a potential resynthesis of this emerging oilseed crop.